Bacterial Composition of Soils in the Fatala River Basin (Guinea) during the Dry Season: An Examination of its Relationship with Ecological Landscape Characteristics - D. A. Ignateva; T. Yu. Gorbunova; I. Keita; Ya. I. Alekseev; R. V. Gorbunov; A. A. Shvartsev; A. A. Volkov; Yu. A. Monakhova; V. A. Tabunshchik; S. Diakité; A. M. Baldé; M. D. Sow; et al. (Юг России: экология, развитие)
This paper examines the bacterial composition of soils in the Fatala River basin, Republic of Guinea.This work is based on molecular genetic analysis.The research findings indicate that the most prevalent phyla are Proteobacteria, Firmicutes, Actinobacteria and Acidobacteria. Notable dominant species include Candidatus Koribacter versatilis and Candidatus Solibacter usitatus. In facies 11, particularly in a bauxite mining zone, there is an increase in cyanobacteria, potentially due to their capacity to enrich soil fertility. Alpha diversity peaks in facies 10, 12, 17 and 18 and bottoms out in facies 7. The decline in alpha diversity in facies 7 might be attributed to the increase in plankomycetes, which produce antimicrobial substances to outcompete other species. When examining beta diversity, facies 10, 12 and 17 show the highest similarity, while facies 3, 5, and 7 exhibit the most significant differences compared to all points analysed.The identification of the prevailing bacterial phylum and dominant species, along with specific taxa exhibiting increases or decreases in biodiversity, is a crucial first step in characterising the microbial communities found in the natural environments studied. The methodology established can be employed in environmental surveillance and evaluation of the health of diverse soil types.